Jejak Pendirian dan Penetapan Bandara Adi Soemarmo sebagai Embarkasi dan Debarkasi Haji di Indonesia, 1974-1997 - Kurniawan, Dadan Adi (UIN Sunan Gunung Djati Bandung, 2024)
This article discusses the background and objectives of the establishment of Adi Soemarmo Airport and the history of its establishment as a center for the departure and return of hajj pilgrims in Central Java Province and the Special Region of Yogyakarta Province. This study uses a historical method consisting of topic determination, heuristics, verification, interpretation and historiography. This paper uses primary and secondary sources in the form of archives, newspapers, books, journals and interviews. The results of the study indicate that Adi Soemarmo Airport was established in 1974 with the aim of being an alternative transportation connecting Surakarta-Jakarta. Another goal is to increase the socio-economic and historical cultural potential in the city of Surakarta and its surroundings. Adi Soemarmo Airport is an enclave civil airport built in a military air base area that has existed since the Dutch colonial era (1940). In 1997, this airport was designated as a center for the departure and return of Hajj pilgrims from Central Java and Yogyakarta. This airport was chosen because it has the most adequate (longest) runway so that it can accommodate the take-off and landing of large aircraft that are usually used to transport hajj pilgrims.